Batting and button-press reaction time in primary, junior high and high school baseball players - Shinya, M.; Komuro, L.; Kobayashi, H.; Obata, H.; Nakazawa, K. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The focus of this study was how baseball players acquire rapid visuo-motor processing during developmental stages. We compared simple and Go/Nogo reaction times in a button-press task and a swing-a-bat task between different age groups of teenage baseball players. Though reaction time, swing time and total reaction time were shorter in the older group, baseball-specific visuo-motor skills could not be investigated by our experiment. These results indicate that the general neural foundations underlying baseball performance develop over the school years.